2004
DOI: 10.1016/j.jmb.2004.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Argininamide Binding Arrests Global Motions in HIV-1 TAR RNA: Comparison with Mg2+-induced Conformational Stabilization

Abstract: The structure and dynamics of the stem-loop transactivation response element (TAR) RNA from the human immunodeficiency virus type-1 (HIV-1) bound to the ligand argininamide (ARG) has been characterized using a combination of a large number of residual dipolar couplings (RDCs) and trans-hydrogen bond NMR methodology. Binding of ARG to TAR changes the average interhelical angle between the two stems from ~47° in the free state to ~11° in the bound state, and leads to the arrest of large amplitude (±46°) inter-he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
128
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(146 citation statements)
references
References 51 publications
(91 reference statements)
18
128
0
Order By: Relevance
“…In contrast, the equivalent A22-U40 base pair in TAR forms only after ligand binding. 23 No significant bend was observed between the two stems which are arranged in near-coaxial stacking as is evident by standard stacking NOEs between C304 to G305. Tertiary contacts in the bulge, for example a cross-strand NOE between a G305 N2 amino proton and the G322 H8 proton as well as our dipolar coupling data define a 60° inter-helical displacement between the two adjacent stems.…”
Section: Structure Of 7sk-sl4 Identifies a Preformed Protein-binding mentioning
confidence: 84%
See 2 more Smart Citations
“…In contrast, the equivalent A22-U40 base pair in TAR forms only after ligand binding. 23 No significant bend was observed between the two stems which are arranged in near-coaxial stacking as is evident by standard stacking NOEs between C304 to G305. Tertiary contacts in the bulge, for example a cross-strand NOE between a G305 N2 amino proton and the G322 H8 proton as well as our dipolar coupling data define a 60° inter-helical displacement between the two adjacent stems.…”
Section: Structure Of 7sk-sl4 Identifies a Preformed Protein-binding mentioning
confidence: 84%
“…17,18 Several NMR studies have elucidated the major conformational transition that argininamide (a tight-binding analog of arginine) induces in the TAR structure upon complex formation. [19][20][21][22][23] In the free form the bulged residues and the terminal A22 and U40 residues are not involved in hydrogen bonding interactions but upon arginine binding U23 and A22 sandwich arginine by forming a critical U23:A27-U38 base-triple and a A22-U40 base pair (Figure 1a, dashed red lines) and leads to a global dampening of interhelical motions. 22,23 The conserved stem loop 4 of 7SK (7SK-SL4) presents significant sequence homology to the TAR RNA from HIV-1 ( Figure 1a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To test this possibility, we examined whether binding of argininamide (ARG), a ligand mimic of TAR's cognate protein target Tat, to the TAR bulge affects relaxation dispersion measured in the apical loop. Previous NMR studies (25,44) showed that ARG binds TAR in and around the bulge stabilizing a coaxial conformation in which bulge residue U23 forms a reverse Hoogsteen base pair with A27-U38 in the upper stem. If our proposed ES2 structure is correct, one would expect that locking the bulge conformation upon ARG binding would quench all relaxation dispersion arising due to exchange with ES2, including in the apical loop.…”
Section: G34-c8mentioning
confidence: 98%
“…These characteristics are the A22:U40 (17, 37) and C30:G34 (17, 38, 39) base pairs; the U23:A27:U38 base triplet (16,17,19,40,41); and the extent of base stacking between the bulge residues U23, C24, and U25 (16,17,37). The CVs for the base pairs and triplet were implemented in a way that measures the number of hydrogen bonds between the residues involved in the interaction.…”
Section: Methodsmentioning
confidence: 99%